1999
DOI: 10.1007/s11661-999-0302-7
|View full text |Cite
|
Sign up to set email alerts
|

A general approach for predicting the drawing fracture load and limit drawing ratio of an axisymmetric drawing process

Abstract: Based on Hill's theory of plasticity and the Swift diffuse instability criterion, new theoretical models are proposed for predicting the drawing fracture load and limit drawing ratio (LDR) of an axisymmtric cup drawing. These models take into account the influence of triaxial stress state, anisotropy, strain hardening, bending, and tool geometry. By introducing both conventional and modified Hollomon's equations, the influences of these variables on the constitutive relation of sheet steels are also analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Before calculating the stress, the constants a, b and n need to be determined. Some investigations 15,16 have indicated that these constants can be calculated using the chemical composition. In the present case, a, b and n are available from data of Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Before calculating the stress, the constants a, b and n need to be determined. Some investigations 15,16 have indicated that these constants can be calculated using the chemical composition. In the present case, a, b and n are available from data of Ref.…”
Section: Resultsmentioning
confidence: 99%